Determination of polyadenylate-rich ribonucleic acid in the nucleus and in the cytoplasm of plasmacytoma cells. - Abraham, K A (1975)
A number of parameters affecting the adsorption of rRNA and poly(A)-containing RNA to Millipore filters were investigated separately. Binding of both types of RNA to the filter was dependent on the concentration of RNA, pH and Mg2+ concentration of the reaction mixture. Both types of RNA bound to the filter optimally at slightly acid pH values. The binding of poly(A)-containing RNA to the filter exhibited a broad pH-dependence compared with that of rRNA. The ratio of poly(A)-rich RNA/rRNA retained by the filter was maximal between pH7 and 8. The presence of 1 mM-EDTA or a high concentration of NaCl (over 0.5M) decreased the affinity of RNA for the filter. The amount of poly(A)-containing RNA in the nucleus and in the cytoplasm of a plasmacytoma cell line (MPC-11) labelled with [32P]Pi was determined by the Millipore-filter technique under conditions that minimized contamination by rRNA. These data were compared with the estimations made by oligo(dT)-cellulose chromatography. The results obtained by these two methods were in good agreement for RNA labelled for short periods (up to 2h). In long labelling and pulse-chase experiments, however, contamination of the filter by rRNA of increasing specific radioactivity in the cytoplasm gave an erroneous value for poly(A)-containing RNA by the Millipore-filter technique. Determinations made on the nuclear fraction by these two methods did not show significant variation in short- and long-term labelling experiments.